2021
DOI: 10.3390/buildings11050205
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Unreinforced Masonry Buildings with Timber Diaphragms

Abstract: Though flexible diaphragms play a role in the seismic behaviour of unreinforced masonry buildings, the effect of the connections between floors and walls is rarely discussed or explicitly modelled when simulating the response of such buildings. These flexible diaphragms are most commonly timber floors made of planks and beams, which are supported on recesses in the masonry walls and can slide when the friction resistance is reached. Using equivalent frame models, we capture the effects of both the diaphragm st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…An analysis of the results of studies of the seismic resistance of buildings shows that many authors studied particular issues of the strength of a building and its individual enclosures. As in our research, the authors of work [16] point to the advisability of using numerical studies of the seismic resistance of brick buildings. The features of the destruction of building enclosures as a result of an earthquake showed that the structural units of the interface of the external enclosures with each other are the most vulnerable.…”
Section: Discussionmentioning
confidence: 63%
“…An analysis of the results of studies of the seismic resistance of buildings shows that many authors studied particular issues of the strength of a building and its individual enclosures. As in our research, the authors of work [16] point to the advisability of using numerical studies of the seismic resistance of brick buildings. The features of the destruction of building enclosures as a result of an earthquake showed that the structural units of the interface of the external enclosures with each other are the most vulnerable.…”
Section: Discussionmentioning
confidence: 63%
“…The second challenge while modeling such buildings are the wooden floors that are usually used. These types of floors are considered very flexible and the connections with the masonry walls are usually not well detailed [61,62]. Consequently, the behavior of the building is quite complex when using the non-linear static pushover analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Perfect fixed restraints were considered at the bases of the walls. A perfect connection has been considered to model the wall to wall connection (Kahrizi and Tahamouli Roudsari 2020;Solarino et al 2019;Tomić et al 2021b).…”
Section: Geometrical Modelmentioning
confidence: 99%